A profile of poverty in Egypt: 1997 - Datt, Gaurav; Jolliffe, Dean; Sharma, Manohar (International Food Policy Research Institute, 1998)
This paper presents a profile of poverty in Egypt for 1997. It assesses the magnitude of poverty and its distribution across geographic and socioeconomic groups, provides information on the characteristics of the poor, illustrates the heterogeneity among the poor, and helps identify empirical correlates of poverty. The poverty profile is constructed using data from the recently completed Egypt Integrated Household Survey, a nationwide, multiple-topic household survey, carried out by the International Food Policy Research Institute in coordination with the Ministry of Agriculture and Land Reclamation and the Ministry of Trade and Supply. Reference poverty lines that take into account regional differences in food and nonfood prices, age and composition of poor households, and food and nonfood consumption preferences are used to determine incidence, depth, and severity of poverty. The characteristics of the poor are analyzed. These characteristics include household composition, dwelling type, educational attainment and access, labor force participation and distribution, child immunization levels, payment transfers, agricultural landholdings, and access to community facilities.